Der Adler : the official Nazi Luftwaffe magazine. (Luftwaffe in combat 1939-45., 2013)
Der Adler was the official magazine of the Luftwaffe in World War II. In the years before Hitler declared war on America an English language edition of Der Adler costing eight cents was published and widely sold in the USA. The magazine was available on American news stands and the surviving English language editions provide readers who do not speak German with a fascinating primary source from inside the Third Reich. The magazine was at its best and most interesting during the years of German ascendancy between 1940 and 1942. From that point onwards the Luftwaffe had less and less to celebr.